Determinants of rural household livelihood dependence on non-timber forest products: A case study from Inanda Community, KwaZulu-Natal, South Africa - Wale, Edilegnaw; Nkoana, Mmaphuti Andrias; Mkuna, Eliaza (Frontiers in Forests and Global Change, 2022)
Natural forest resources are the most accessible sources of services, products and incomes for many adjacent rural communities. However, the declining resilience of forests and agricultural sectors particularly in South Africa is concerning and a real public policy challenge. Little is known about the determinants of rural community dependence on natural forests, and the importance of this dependence to rural livelihoods and environmental outcomes. This study investigated factors affecting rural household level of forest dependence and the contribution of natural forests to rural household livelihoods in the “KwaZulu-Natal Sandstone Sourveld (KZNSS)” ecosystem. Employing survey data from 150 forest-dependent households and a logit-transformed Ordinary Least Squares (OLS) model, the study found that there is significant level of forest dependence in the study area. The empirical findings showed that the contribution of forest resources to rural livelihoods is significantly influenced by off-farm incomes, employment incomes, forest vouchers received from the “Wildlands Project” in exchange for planting trees, values of household assets, changing of time and dates in visiting the forest for the collection of forest products, and perceived changes in temperature. These findings imply that institutional arrangements for programs like the “Wildlands Project” need to be developed from the beginning with the participation of all pertinent stakeholders for everyone to accept it and understand the regulations. Additionally, legislative changes are needed to help rural residents sustainably support their livelihoods and diversify their sources of income to build resilience and ease pressure on natural forests.